Análise da duração de acidentes de trânsito em vias arteriais de Fortaleza-Ce - Souza, Vandeyberg Nogueira de (2019)
The impact of traffic accidents on urban congestion is strongly correlated with their duration. Therefore, understanding the characteristics of this duration and the factors that influence it is extremely important for the development of efficient traffic control strategies. Aiming to contribute to this problem, this research aimed to analyze the duration of traffic accidents that occurred on arterial urban roads, using as a case study the city of Fortaleza-CE. For the development of the work was used a database of traffic accidents occurred in Fortaleza, from 2015 to 2017, with information such as: the reported time of the accident, location, nature, severity and number of vehicles involved, among others. Since the database obtained does not have information on the duration of accidents, one of the specific objectives of this work was to develop a method to extract this information from traffic data recorded by electronic surveillance equipment. From the developed method, we obtained a sample with information of 324 traffic accidents. The average duration verified for the analyzed accidents was 72 minutes, with a standard deviation of 48 minutes, indicating a high variability in the duration of the accidents. The individual influence of potential factors explaining the duration of accidents was tested by visual analysis of the survival curve of these factors and the nonparametric Kruskal-Wallis test. The results showed significant influence of the zone in which the accident occurred (center or periphery), the period (peak or off peak), the location (intersection or mid block) and the number of vehicles involved. To analyze the joint influence of the potential explanatory factors on the variability of accident duration, the Hazard Based Model was used to study the conditional probability of a given event ending soon, since this event has already lasted. a known time. The results showed the significant influence of four factors on the duration of accidents: Zone, Period, Number of vehicles involved and severity. The number of vehicles involved in the accident was the factor of greatest impact on their duration. From the results obtained, it is possible to raise hypotheses such as: (i) traffic agents prioritize the solution of accidents that occur in the city center because it has higher traffic; (ii) the number of agents available at peak hours may not be sufficient for the time demand.